2018
DOI: 10.1007/s00404-018-4999-7
|View full text |Cite
|
Sign up to set email alerts
|

MiR-424-3p suppresses galectin-3 expression and sensitizes ovarian cancer cells to cisplatin

Abstract: PurposeAssessment of miR-424-3p mimic capability to sensitize SK-OV-3 and TOV-21G ovarian cancer cells to cisplatin by decreasing the expression of galectin-3, which is an anti-apoptotic protein overexpressed in ovarian cancer and associated with resistance to chemotherapy.MethodsWe performed a reverse transfection of miR-424-3p mimic into SK-OV-3 and TOV-21G ovarian cancer cells, followed by Real Time™ RT-PCR analysis of the expression of miR-424-3p and galectin-3 mRNA as well as ELISA assay for galectin-3 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Niu et al demonstrated that the expression of miR-509-3p was significantly downregulated in cisplatin-resistant ovarian cancer tissues, and that this miRNA can sensitize ovarian cancer cells to cisplatin by the downregulation of the expression of Golgi phosphoprotein-3 and wntless Wnt ligand secretion mediator 22 . Dominik et al revealed that miR-424-3p sensitizes ovarian cancer cells to cisplatin through decreases in the expression of galectin-3 23 . Since miRNAs do not require perfectly complementary target sites, a single miRNA regulates hundreds of genes, and a single oncogene is regulated by hundreds of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Niu et al demonstrated that the expression of miR-509-3p was significantly downregulated in cisplatin-resistant ovarian cancer tissues, and that this miRNA can sensitize ovarian cancer cells to cisplatin by the downregulation of the expression of Golgi phosphoprotein-3 and wntless Wnt ligand secretion mediator 22 . Dominik et al revealed that miR-424-3p sensitizes ovarian cancer cells to cisplatin through decreases in the expression of galectin-3 23 . Since miRNAs do not require perfectly complementary target sites, a single miRNA regulates hundreds of genes, and a single oncogene is regulated by hundreds of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…50 In our study, the expression of miR-424 in DDP resistant group was significantly decreased in compared with the DDP chemosensitive group, which was consistent with other research. 51,52 In present study, hub genes were screened by the plug-in CytoHubba, among the top 10 hubgenes in downregulation miRNA group, 8 of them were identified as the target genes of miRNA-424(CDC27, CDC23, RNF213, SMURF1, SMURF2, UBE4A, LMO7, WSB1), the hub gens were continued to be screened by Coremine Medical online database. Coremine Medical is a domainspecific search engine for medical information, which was based on a new search concept that offers the user domainspecific networks.…”
Section: Discussionmentioning
confidence: 99%
“…Protein levels of GAL‐3 can be modulated by specific micro‐RNA molecules (miR) (Ramasamy et al, ). In this regard, a very recent elegant study has shown that miR‐424‐3p (known as miR‐322) can degrade GAL‐3 in SKOV3 without altering its mRNA transcription and rendered these tumor cells more sensitive to cisplatin‐induced cell death (Bieg et al, ). Similarly, but in lung cancerous cells, miR‐424‐3p inhibited cell migration, invasion, and proliferation and enhanced their sensitivity to cisplatin and paclitaxel (Zhang, Zeng, Zhao, & Liu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Primers used to study mRNA levels of GAL‐3, and miR‐424‐3p (Acc. # NM_002306.3) were adopted from the study of Bieg, Sypniewski, Nowak, and Bednarek (). The primer pairs used to study mRNA of β‐actin (Acc.…”
Section: Methodsmentioning
confidence: 99%